Experiência subjetiva de idosas durante exercício em ambiente virtual - Do Nascimento, Amanda Mayara [UNESP]; Rodrigues, Nara Heloisa [UNESP]; Andrade, Eric Francelino; Rogatto, Gustavo Puggina; Schwartz, Gisele Maria [UNESP]; Valim-Rogatto, Priscila Carneiro (FapUNIFESP (SciELO), 2013)
This quali-quantitative study aimed to verify subjective exercise experiences of older women before and after exercise sessions in actual and virtual conditions, as well as, the preferred exercise condition. The sample was composed by 20 older women (71.1±6.5 years-old) who practiced dance sessions in actual and virtual conditions, and answered the Subjective Exercise Experiences Scale (SEES) before and after the activity. In virtual condition it was used the virtual game Just Dance I from the Nintendo Wii® console. In actual condition participants reproduced the same game movements, as demonstrated by the researcher. Wilcoxon and Mann-Whitney tests were used for data analyses (p<0.05). Significant decrease was observed in the psychological distress score of SEES after both conditions. Increase in positive well being score was found only in the virtual condition. Most of the older women chose the actual condition as the preferred.

Os objetivos desse estudo quali-quantitativo foram verificar as experiências subjetivas relacionadas ao exercício em idosas antes e depois da realização de atividade física em ambientes real e virtual, bem como a preferência pelo ambiente. A amostra foi composta por 20 idosas (71,1±6,5 anos) que executaram sessões de dança nos dois ambientes e responderam ao instrumento Subjective Exercise Experiences Scale (SEES) antes e depois da prática. Na situação virtual foi utilizado o jogo Just Dance I do console Wii® da Nintendo. Na situação real, cada participante reproduziu os mesmos movimentos demonstrados pela pesquisadora. Para a análise dos dados da SEES foram utilizados os testes Wilcoxon e Mann-Whitney (p<0,05). Houve redução significativa na pontuação da subescala distress psicológico da SEES após ambas as situações experimentais e aumento no bem-estar positivo apenas em ambiente virtual. A maioria das idosas escolheu o ambiente real como o preferido.
Subjective experience of older women during exercise in virtual condition
Experiencia subjetiva de mujeres ancianas durante el ejercicio en el ambiente virtual
Keywords: Aging; Behavior; Exercise; Technology